Diseño de órtesis activa dinámica que permite la movilidad del brazo y antebrazo, en niños de 3 a 6 años - Aguilar-Castillo, Vanessa; Fernández-Garza, Eugenia (Instituto Tecnológico de Costa Rica, 2016)
Design development active dynamic orthosis for assisted mobility of superior members, when children 3 to 6 years with little or no ability to move their arms, allowing them to maintain a position and oscillate in it.
Proyecto de Graduación (Bachillerato en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Industrial, 2016.
Keywords: Tecnología; Extremidades; Patología; Dispositivos; Prótesis; Research Subject Categories::TECHNOLOGY::Other technology::Medical engineering